2022
DOI: 10.15282/ijame.13.2.2016.10.0282
|View full text |Cite
|
Sign up to set email alerts
|

Classification of crankshaft remanufacturing using Mahalanobis-Taguchi system

Abstract: Remanufacturing is a process of returning a used product to at least its original performance with a warranty that is equivalent or better than that of a newly manufactured product. During a preliminary inspection on remanufacturing companies, it was found that there is no end life for crankshafts in terms of classifying it either to remanufacture, repair or reject due to limited information provided by the original equipment manufacturer. The manufacturer did not provide any information on the annual quantity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This work is actually a continuation of the research done by Abu et al [23] of a classified EOL crankshaft into rejected, repairable and remanufacturable. Generally, the ABC system includes allocation of indirect costs to centres, costs from centres to activities and costs from activities to cost objects.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…This work is actually a continuation of the research done by Abu et al [23] of a classified EOL crankshaft into rejected, repairable and remanufacturable. Generally, the ABC system includes allocation of indirect costs to centres, costs from centres to activities and costs from activities to cost objects.…”
Section: Methodsmentioning
confidence: 58%
“…Similarly, Shigaev [22] applied the ABC approach to give a better insight in the actual cost structure of a positron emission tomography procedure by defining the constituting components and simulating the impact of possible resource or practice changes. In the case of gall bladder surgeries, ABC approach is proven to be an effective cost management model that determined costs and evaluated financial performance across departments [23]. In a work by Jusoh and Miryazdi [24], the authors described the case of the realisation of a two-stage cost allocation scheme of ABC and related customer profitability report at a distribution company.…”
Section: Introductionmentioning
confidence: 99%
“…There are several automotive components that have potential for multiple life-cycles, such as clutches, brake shoes, engine block, starters, alternators, water pumps and carburettors [37,69]. Besides that, the remanufacturing of automotive products is an effective strategy to promote sustainability in the automotive industry because, compared to new products, remanufactured products only cost 50% of the cost for new products, utilise 60% of energy and 70% [70], Therefore, an engine was used as a case example in this study. As there are too many design requirements and some of the requirements are conflicting [56], the design requirements have been analysed from a review of 25 publications as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Abu et al [29] provided a systematic pattern recognition using MTS by constructing a scatter diagram that could support decision making of a particular industry on 14 prominent journals of crankshaft belonging to 7 engine models with differrent numbers of samples. Abu et al [30] classified crankshafts' end life into recovery operations based on the Mahalanobis-Taguchi system. Nik Mohd Kamil and Abu [31] developed a distinctive pattern of the crankshaft and identified crankshaft's critical and non-critical parameters based on the MTS, then applied the Activity Based Costing (ABC) as a method of estimation for the remanufacturing cost of the crankshaft.…”
Section: Literature Reviewmentioning
confidence: 99%